2010
DOI: 10.1007/s00213-010-1835-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained stress-induced changes in mice as a model for chronic depression

Abstract: This study shows region-specific long-term neurobiological adaptations induced by CMS and residual hippocampal signs after paroxetine treatment. We propose the use of this model to study molecular mechanisms involved in chronic depression and vulnerability for relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 65 publications
(80 reference statements)
8
54
0
Order By: Relevance
“…It will be important to identify the proteins that are up regulated in c-Fos-ir neurons after caffeine administration. It has been shown that repeated stress or chronic stress results in less c-Fos expression (Badowska-Szalewska et al 2006;Girotti et al 2006;Elizalde et al 2010). Correspondingly, we identified that repeated doses of caffeine result in an attenuation of c-Fos protein expression.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It will be important to identify the proteins that are up regulated in c-Fos-ir neurons after caffeine administration. It has been shown that repeated stress or chronic stress results in less c-Fos expression (Badowska-Szalewska et al 2006;Girotti et al 2006;Elizalde et al 2010). Correspondingly, we identified that repeated doses of caffeine result in an attenuation of c-Fos protein expression.…”
Section: Discussionsupporting
confidence: 65%
“…Our data showing that the repeated and chronic effect of caffeine attenuates signal transcription in the immediate early gene-mediated pathway agrees with the data of Svenningsson and Fredholm (1997) who showed that repeated administration of caffeine reduces c-fos mRNA expression in the globus pallidus. Moreover, chronic stress induced the down-regulation of glutamic acid decarboxylase-65 (GAD65) and vesicular glutamate transporter1 (vGlut1) expression (Elizalde et al 2010). We suggest that repeated doses of caffeine suppress either adenosine receptor expression or glutamate receptor expression.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with previous reports (Briones et al 2012;Elizalde et al 2010), the present study shows that depressive phenotype of anhedonia is observed as later as 7 weeks in Wistar rats, which is not in agreement with previous observations in Lister hooded or Sprague Dawley rats (D'Aquila et al 1994;Grønli et al 2004). This disagreement may be related to different animal strains (Lister hooded or Sprague Dawley versus Wistar rats) and sucrose dose (1 % versus 2 %).…”
Section: Discussionsupporting
confidence: 55%
“…Also, CMS was shown to downregulate expression of BDNF and activation of cAMP-response element binding protein (CREB), both involved in the pathophysiology of depression and the mechanism of action of antidepressants (Hu et al 2010). CMS was also shown to suppress adult hippocampal cytogenesis, which has been suggested to play a role in depression (Elizalde et al 2010;Schoenfeld and Cameron 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In support of this theory, a study on the role of SNCA showed a significant decrease in the frequency of miniature excitatory postsynaptic potentials in mice overexpressing human SNCA (68). Furthermore, the decrease in hippocampal GABA levels seen in studies on mice exposed to CMS could also be explained by a deficit in vesicular function (69,70).…”
Section: Discussionmentioning
confidence: 58%